Seeking the Roles for Fungal Small-Secreted Proteins in Affecting Saprophytic Lifestyles - Feldman, Daria (Front Microbiol, 2020)
Small secreted proteins (SSPs) comprise 40–60% of the total fungal secretome and are present in fungi of all phylogenetic groups, representing the entire spectrum of lifestyles. They are characteristically shorter than 300 amino acids in length and have a signal peptide. The majority of SSPs are coded by orphan genes, which lack known domains or similarities to known protein sequences. Effectors are a group of SSPs that have been investigated extensively in fungi that interact with living hosts, either pathogens or mutualistic systems. They are involved in suppressing the host defense response and altering its physiology. Here, we aim to delineate some of the potential roles of SSPs in saprotrophic fungi, that have been bioinformatically predicted as effectors, and termed in this mini-review as “effector-like” proteins. The effector-like Ssp1 from the white-rot fungus Pleurotus ostreatus is presented as a case study, and its potential role in regulating the ligninolytic system, secondary metabolism, development, and fruiting body initiation are discussed. We propose that deciphering the nature of effector-like SSPs will contribute to our understanding of development and communication in saprophytic fungi, as well as help, to elucidate the origin, regulation, and mechanisms of fungal-host, fungal-fungal, and fungal-bacterial interactions.